Constellations of weathering: following the meteorological mobilities of Bangla bricks. Issue 6 (1st November 2020) - Cullen, Beth
ABSTRACT: Using follow-the-thing methods and insights from ethnographic fieldwork, this paper traces the meteorological mobilities entwined within Bangladesh bricks. Following the extended lifecycle of the Bangla brick from sediment to clay, from clay to brick and from brick to sediment, and the role that monsoon weathering plays in these processes, reveals complex entanglements of mobilities and materialities. A more-than-human mobilities perspective highlights the myriad human and nonhuman circulations that constitute the brick, as well as the geological, atmospheric and hydrological dynamics that brickmaking sets in motion. Through the becoming and unbecoming of the brick, the paper explores how the mobile materiality of the monsoon is enmeshed within the building blocks of Bangladesh's cities and the infrastructures on which they depend and how, in turn, the mobile materiality of the brick influences monsoonal environments. These intra-active entanglements trouble perceived dichotomies between society and meteorological forces and highlight the agentive role of weather systems in social worlds.